The Prevalence of Occult Hepatitis B Virus in the Hemodialysis Patients in Yazd, Iran - Jamshid Ayatollahi; Somayeh Jahanabadi; Mohammad Sharifyazdi; Roya Hemayati; Mahmood Vakili; Seyed Hossein Shahcheraghi (Acta Medica Iranica, 2017)
Occult HBV infection of hemodialysis (HD) patients is informative in terms of virus transmission. It may be of clinical importance in HD patients. The aim of this study was to investigate the prevalence of anti-HBc in the HD Patients. Number of 126 patients undergoing hemodialysis were included in this study from main hemodialysis units in Yazd. Hepatitis B surface antigens (HBsAg), hepatitis B core antibody (anti-HBc) were examined in all subjects. Finally, stored serum samples from anti-HBcAb positive, HBsAg negative patients were anonymised and tested for HBV DNA by real time quantitative PCR assay. The age range of the patients was 17-88 years. Of the 126 patients, 123 patients (97.6%) were HBC-Ab negative and 3 (2.4%) were positive. Of 3 patients with Anti-HBC positive, HBV DNA was detected in 1 patient. This study showed a low rate of isolated anti-HBc (2.4%). HBV DNA was also detected in 1 patient.